Monitoring of the Condition of Green Plantations in Shevchenkivskyi District of Kharkiv (on The Example of Bittle Chestnut (Aesculus Hippocastanum L.) - Maksymenko , N. V.; Gololobova , O. O.; Koval, I. M.; Kalynovskyi , O. I. (Man and Environment. Issues of Neoecology, 2021)
In the complex of measures for improving atmospheric air quality in a modern city and reduction of noise pollution, special emphasis is placed on outdoor green spaces, which primarily perform a sanitary and hygienic function, protect residents and urban sites from harmful transport emissions, localization and partially absorb them. Purpose. Monitoring the state of green spaces in the Shevchenkivskyi district of Kharkiv (for example, bitter chestnut (Aesculus Hippocastanum L.) Methods. Analytical and synthetic method, geoinformation (cartographic modeling and processing of remote sensing data), analysis of information sources and methods of field research. Results. Based on the analysis of literature and fund materials and our own field research, information was obtained on the current state of plantings of common bitter chestnut in the Shevchenkivskyi district of Kharkov. A visual assessment of the quality of common bitter chestnut stands was made, in particular, damage to trees was determined. An inventory map of urban plantations of bitter chestnut in the usual Shevchenkivskyi region was developed using GIS technologies. Recommendations have been developed to improve the ecological state of common bitter chestnut plantations within the Shevchenkivskyi district of Kharkiv. Based on the results of this study and taking into account the preliminary work of scientists, it has been proved that the development of an inventory map of urban plantings of common bitter chestnut makes it possible to find out information about the state of the city’s green spaces (number, types, age, diseases and damage, etc.). Conclusion. The obtained data on green spaces can determine the priorities for the development of landscape design, an action plan for urban green infrastructure to adapt to climate change. Based on reliable data, you can draw up a quality plan for the development of urban greening.